Overview of steel slag application and utilization - Lim, Jin Wei; Chew, L. H.; Choong, Thomas Shean Yaw; Cionita, Tezara; Yazdi, Mohammad Hossein (EDP Sciences, 2015)
Significant quantities of steel slag are generated as waste material or byproduct every day from steel industries. Slag is produced from different types of furnaces with different operating conditions. Slag contains Ferrous Oxide, Calcium Oxide, Silica etc. Physical and chemical properties of slag are affected by different methods of slag solidification such as air cooled, steam, and injection of additives. Several material characterization methods, such as X-ray Diffraction (XRD), Scanned Electron Microscopy (SEM) and Inductive Coupled Plasma (ICP-OES) are used to determine elemental composition in the steel slag. Therefore, slags can become one of the promising materials in various applications such as in transportation industry, construction, cement production, waste water and water treatment. The various applications of steel slag indicate that it can be reused and utilized rather than being disposed to the landfill. This paper presents a review of its applications and utilization.